2004
DOI: 10.1007/bf02479636
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of silica fume blended cement hydration

Abstract: A model is proposed in this paper to simulate silica fume (SF) blended cement hydration based on the kinetics, stoichiometry and physical chemistry of cement hydration and pozzolanic reaction. The pozzolanic reaction degree, volume fraction of hydration products, capillary porosity and gel porosity can be obtained from model simulation. By using proper amount of silica fume replacement, the microstructure of silica fume blended cement paste is improved since the volume fraction of C-S-H gel is increased, Ca(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In this study, it is assumed that the pozzolanic reaction of SF takes place according to Equation (11). This assumption has been adopted successfully in many simulations and calculations involving SF (Bentz, 2000;Bentz et al, 2000;Swaddiwudhipong et al, 2003;Yajun and Cahyadi, 2004).…”
Section: Reaction Of Sf In Binary Pastementioning
confidence: 99%
“…In this study, it is assumed that the pozzolanic reaction of SF takes place according to Equation (11). This assumption has been adopted successfully in many simulations and calculations involving SF (Bentz, 2000;Bentz et al, 2000;Swaddiwudhipong et al, 2003;Yajun and Cahyadi, 2004).…”
Section: Reaction Of Sf In Binary Pastementioning
confidence: 99%
“… where is the hydration of silica fume, is the SF affinity which is given in the equation (64) , is the activation energy of SF, is the material constant, which is given in the equation (65) . where , and are the experimentally computed material constants are given by Yajun [44] . is the ultimate degree of SF reaction, this is defined in equation (66) given by Yajun [44] and Luzio [43] .…”
Section: Theorymentioning
confidence: 99%
“… where , and are the experimentally computed material constants are given by Yajun [44] . is the ultimate degree of SF reaction, this is defined in equation (66) given by Yajun [44] and Luzio [43] . and According to Yajun [44] , all the calcium hydroxide (CH) produced during the cement hydration can consumed by the pozzolanic reaction when sufficient amount of SF available in the mixture.…”
Section: Theorymentioning
confidence: 99%
“…Property evolution of nanoSiO 2 -added cementitious materials can be reflected by the effects of nanoSiO 2 on cement hydration, gel property modification, and pore structure refinement [3,[13][14][15][16]. Results have shown that the strength enhancing effect of nanoSiO 2 in the early age is related to its hydration acceleration effect, but its effects in the later age have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%